A Rare Case of Vanishing Bone Disease of Metacarpals - Kamble, Prashant (J Orthop Case Rep, 2021)
INTRODUCTION: Vanishing bone disease is rare phenomenon of idiopathic origin that leads to extensive osteolysis of bone. Prognosis of disease is unpredictable and definitive guidelines for management are still unknown. The vanishing bone disease has been reported for multiple other bones, however, this probably is the 1st time that vanishing bone disease of the metacarpals is being reported. CASE REPORT: A 22-year-old male presented with shortening middle finger and poor grip strength of the left hand. Serial radiographs revealed progressive concentric reduction of third and then fourth metacarpal shaft, with a sucked candy appearance. All the blood parameters were normal including calcium and parathormone levels. There was no evidence of any tumor elsewhere in the body. Biopsy showed myxoid areas, proliferating vessels interposed with skeletal muscles. Thus, based on clinical, radiological, and histopathological findings, we made the diagnosis of vanishing bone disease. The patient was treated with autologous non-vascularized fibula graft and was fixed with transverse k-wires to adjacent metacarpals. At 2-year follow-up, graft was completely incorporated and the patient gained full functional recovery. CONCLUSION: Vanishing bone disease affecting the metacarpals is very rarely reported in the literature. The diagnosis should be made by excluding all the other conditions such as primary bone tumors or secondary from other sites. There are no fixed treatment guidelines. However, we could treat this condition successfully with autologous non-vascularized fibular graft.